Quantitative Ethnomedicinal Survey of Wild Edible Fruits Used by the Indigenous Community in North Waziristan, Khyber Pakhtunkhwa, Pakistan - Rehman, Sabith; Iqbal, Zafar; Qureshi, Rahmatullah; Mujtaba Shah, Ghulam; Afzal, Aftab; Ur Rahman, Khursheed; Hussain, Wahid; Younas, Muhammad; Latif, Saba; Siddiqa, Ayesha; Hussain Shah , Syed Sabir (Ethnobotany Research and Applications, 2024)
Background: This study documented ethnomedicinal importance of wild edible Fruits (WEFs) from the wild floristic emporium of North Waziristan, Khyber Pakhtunkhwa, Pakistan. There is good diversity of plant species in the studied area which are being used for therapeutic purpose for a wide range of applications. Methods: Ethnomedicinal data was collected through face-to-face interviews and semi-structured questionnaires. Various ethnobotanical indices such as Relative frequency of citation (RFC), Use value (UV), Fidelity level (FL), and Jaccard index (JI) were used for calculating values for the WEFs, diseases treated, and important fruit species based on use reports by the informants. Results: A total of 57 species of WEFs belonging to 35 families were reported to be used in traditional medicines. Rosaceae Family was dominated in the area with 6 species, followed by Fabaceae (5 spp.), and Moraceae (4 spp.) with mostly tree-type growth form (49.12%). The most consumed part of plants was fruits (84.48%) used in making folk recipes, followed by seeds (15.52%). Using raw (33.33%) and powder (24.64%) formation were the major modes of crude drug preparation. The highest RFC value was reported for Morus nigra (0.36), followed by Morus alba (0.35). Conclusions: The tradition of using WEFs in curing ailments is common in practice among the tribal people of North Waziristan, depending on the socio-economic conditions of the community. The multiple uses of these WEFs augments for further investigation regarding pharmaceutical applications and phytochemical analysis. Keywords: Indigenous Knowledge, Wild edible fruits, Floristic emporium, Ethnobotany, North Waziristan, Pakistan.